Embodied Learning in Early Mathematics Education: Translating Research into Principles to Inform Teaching - Jennifer Way; Paul Ginns (MDPI AG, 2024)
There exists a substantial body of research evidence that embodied learning modes can enhance children's mathematics learning, yet implementation of the research findings in classrooms has so far been limited. This paper argues the need for translational research to bridge the gap between psychological, neuroscientific, and narrow-focused educational research and teaching practice in schools. As a foundation for such research, and with a focus on early year mathematics education (4 to 8 years), we derive a set of 12 principles of embodied learning from the research literature by applying an integrative literature review method. Based on the findings from the literature, we offer some advice on how these principles might be put into practice with young students.